STUDI EVALUASI ADMINISTRASI GURU KELAS - Debby Arianti (UNIVERSITAS BENGKULU, 2015)
The purpose of this study to evaluation the suitability between clasroom teacher administration in elementary school number 56 Lubuklinggau city with the established standards. The method of this research was descriptive evaluative. The subject of this research are classroom teacher. The data were collected by means of observation, interview and documentation. The result showed the classroom teacher have not complete document, document preparation process conducted jointly by teachers, principals, administrators in accordance with the functions and roles of each, and suitability the charging documents with the established standards is not suitable.Conclusions this reasearch, the administrative documents classroom teacher is not suitable with the established standards.Keyword: evaluation study, classroom teacher, administration